Konsep Kafa’ah Dalam Hukum Islam (Studi Komparasi Pemikiran Antara Imam Syafi’i Dalam Kitab Al - Umm Dan Imam Ibnu Hazm Dalam Kitab Al-Muhalla) - Moch. Aufal Hadliq KMW, Tasfiyatul Fikriyah (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
Kafa'ah is balance, harmony, and harmony, or equality. Equality here refers to the piety of someone who eliminates distinctions, not about caste equality, let alone wealth equality. Because if kafa'ah is defined as equality in terms of wealth, or nobility, it will mean the formation of caste, whereas in Islam there is no justification for caste, because humans on the side of Allah SWT are all the same. Only piety makes the difference. Kafa'ah in marriage is a factor that encourages the creation of husband and wife happiness, and ensures the safety of women from failure or shock in the household. In determining kafa'ah, Imam Shafi'i and Ibn Hazm have different opinions, Imam Shafi'i argues that kafa'ah is a requirement in the usual marriage, not a condition for the validity of marriage. Meanwhile, Ibn Hazm absolutely rejected the existence of kafa'ah. The results of this study indicate that (1) the concept of kafa'ah according to Imam Syafi'i is to equalize the position of the prospective groom and prospective bride. In determining the size of sekufu' it is not just faith but lies in religion, lineage, status of independence, occupation, and the absence of defects that allow kyiar. While the concept of kafa'ah according to Imam Ibn Hazm kafa'ah does not exist in Islam, because Muslims are equal in position, brothers to one another. (2) The concept of kafa'ah between Imam Shafi'i and Ibn azm has similarities and differences. In matters of religion as a criterion for kafa'ah they both use it, it's just that the application is different.